Comparison of Cervical Cancer Screen Results on Female-to-Male Transgender Patients With Female Patients. Issue 4 (7th October 2021) - Davis, Katelynn; Kwon, Regina; Graham, Ashleigh; White, Marissa; Maleki, Zahra; Rodriguez, Erika
Abstract: Objectives: There are limited data on cervical screen results from female-to-male (FTM) transgender patients. Herein, we compiled demographic information and cervical screen testing on FTM transgender patients and compared with age-appropriate controls. Methods: A search of our previous and current databases was performed for Papanicolaou (Pap) tests from patients taking testosterone and/or with a diagnosis of gender dysphoria, transsexualism, or transvestism. Patient data were reviewed. Relative risks of abnormal Pap smear and human papillomavirus (HPV) infection were calculated against age-matched controls. Results: Eighty-nine Pap tests from FTM transgender individuals were identified, with a mean age of 31.3 years (range, 21-60 years). The Pap test diagnoses were distributed as follows: negative for intraepithelial lesion (n = 84, 94.4%), atypical squamous cells of undetermined significance (n = 0), low-grade intraepithelial lesion (n = 4, 4.5%), and high-grade squamous intraepithelial lesion (n = 1, 1.1%). Fifty (56.2%) patients had concurrent high-risk HPV testing with four (8%) positive results. Relative risk was 0.625 (95% confidence interval [CI], 0.25-1.59; P = .32) for an abnormal Pap test and 0.55 (95% CI, 0.19-1.52; P = .24) for HPV compared with 267 age-matched controls. Of note, 13.5% of patients older than 21 years had documentation of never having a prior Pap test in our medical record. Conclusions: In our study, FTM transgender individuals were not at a higher or lower risk of HPV infection or abnormal Pap test result compared with women. However, larger studies are needed to support our findings.